IbM TEMPE BEKATUL PREBIOTIK - Anis Nurhidayati; Agnes Sri Harti; Rahajeng Putriningrum (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Rice brand of tempeh is one way of food fortification based fermented soy beans , which had been added with rice bran. Dependence on imported soybean production impact to high cost of raw materials and product. The concept of food fortification is used for the characterization of foods biosuplemen health improvement as a functional food . Therefore efforts should be done to substitute the yellow soybean seeds using other raw materials that are safe, nutritious and economical as was as rice bran and Chito - oligosaccharides ( COS ) . One form is a novelty that can be developed as biosuplemen prebiotic prebiotic natural healthy and highly nutritious . Krajan is one of the industrial centers tofu located in Kalurahan Mojosongo , District Jebres , Surakarta, Central Java Province . In this area there are more than 100 entrepreneurs tofu every day on average to process 250 kg of soybeans into tempeh . The UKM partners that will be used for this program are named UKM " Dele Mas " and UKM " Moelyo Santoso ". The purpose of the activities is to apply the COS and rice bran as a preservative and a natural prebiotic in the production of soybean bran on the partners to become a comprehensive program of activities and sustainable . Keywords: Community service program, rice bran, chitosan, tempeh